Impact of intercropping grass on the soil rhizosphere microbial community and soil ecosystem function in a walnut orchard - Wang, Changxi; Liang, Qiang; Liu, Jianning; Zhou, Rui; Lang, Xinya; Xu, Shengyi; Li, Xichen; Gong, Andi; Mu, Yutian; Fang, Hongcheng; Yang, Ke Qiang (Frontiers in Microbiology, 2023)
The intercropping of grass in orchards has beneficial effects on soil properties and soil microbial communities and is an important soil management measure for improving orchard productivity and land-use efficiency. However, few studies have explored the effects of grass intercropping on rhizosphere microorganisms in walnut orchards. In this study, we explored the microbial communities of clear tillage (CT), walnut/ryegrass (Lolium perenne L.) (Lp), and walnut/hairy vetch (Vicia villosa Roth.) (Vv) intercropping system using MiSeq sequencing and metagenomic sequencing. The results revealed that the composition and structure of the soil bacterial community changed significantly with walnut/Vv intercropping compared to CT and walnut/Lp intercropping. Moreover, the walnut/hairy vetch intercropping system had the most complex connections between bacterial taxa. In addition, we found that the soil microorganisms of walnut/Vv intercropping had a higher potential for nitrogen cycling and carbohydrate metabolism, which may be related to the functions of Burkholderia, Rhodopseudomonas, Pseudomonas, Agrobacterium, Paraburkholderia, and Flavobacterium. Overall, this study provided a theoretical basis for understanding the microbial communities associated with grass intercropping in walnut orchards, providing better guidance for the management of walnut orchards.